A Response to a Query Regarding a Recent Article: Always Follow Your Results. Issue 5 (September 2018) - Hunter, Michael; Brine, Patrick; Cutrona, Anthony
Abstract : A response to a specific question regarding the content of the recent article "Always Follow Your Results: Ulcerative Lesions and Night Sweats in an Intravenous Drug User."